Magnetically separable core–shell ZnFe2O4@ZnO nanoparticles for visible light photodegradation of methyl orange. (May 2016) - Kulkarni, Suresh D.; Kumbar, Sagar; Menon, Samvit G.; Choudhari, K.S.; C., Santhosh
Graphical abstract: Highlights: Phase pure, magnetic ZnFe2 O4 @ZnO nanoparticles synthesized with excellent yield. ZnFe2 O4 @ZnO displayed higher UV photocatalytic efficiency than ZnO nanoparticles. First report on visible light photodegradation of methyl orange by ZnFe2 O4 @ZnO. Excellent reusability of ZnFe2 O4 @ZnO nanoparticles observed for azo dye removal. Abstract: Visible light photodegradation of aqueous methyl orange using magnetically separable core–shell ZnFe2 O4 @ZnO nanoparticles is reported. A combination of low temperature (190 °C) microwave synthesis and hydrothermal method were used to prepare phase pure material with excellent yield (95%). The magnetic separability, surface area of 41 m 2 /g and visible light absorption make ZnFe2 O4 @ZnO nanoparticles a good solar photocatalyst. ZnFe2 O4 @ZnO displayed greater UV photocatalytic efficiency than ZnO owing to the generation of large number of electron-hole pairs. Visible light photodegradation of MO using ZnFe2 O4 @ZnO nanoparticles is reported for the first time. Higher first order rate constants under both UV and visible light for core-shell nanoparticles suggested their superiority over its individual oxides. The ZnFe2 O4 @ZnO showed excellent reusability with high photocatalytic efficiencies suggesting its suitability for solar photocatalytic applications.